Sоmato-visceral correlation of the sphincter apparatus of the extrahepatic bile ducts in the second trimester of human intrauterine development - Tsyhykalo O.V. (Морфологія, 2009)
Seventy two unfixed bodies of 4-6-month old human fetuses have been studied by means of a complex of methods of a morphologic research (somatoscopy, anthropometry, contrast radiography) and a statistical analysis. It has been established that during the second trimester of the intrauterine development a tendency towards a lover skeletopic position and the larger diapason of the individual position of the sphincter components of the extrahepatic bile ducts (EBD) in the fetuses of male gender is traced compared with the fetuses of the female gender of the same parietocalcaneal length. The skeletopy of the sphincter components of the EBD reliably correlates with the somatotype of the fetuses. Asymmetric dynamics of changes of the skeletopy of the sphincter components of the EBD is traced in the fetuses from the beginning of 6th month of development and depend on the somatotype of fetuses. The periods from the end of the 4th and to the beginning of the 5th months and the beginning of the 6th month may be considered to be critical in the development of the sphincter components of the EBD as a time of appearance of variants of its structure and a feasible appearing of malformations.